Transparansi dan Akuntabilitas Pengelolaan Dana Bantuan Operasional Sekolah (BOS): Studi Kasus di Daerah Terpencil - Adekamisti, Revi; Syamsir, Syamsir; Hamengkubuwono, Hamengkubuwono; Istan, Muhammad (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2025)
Reports and transparency need to be done by all leaders, so that everyone can know and be part of the supervision in the use of BOS funds. Not only is transparency done by developed regions, but transparency also needs to be done in remote areas. This study aims to examine the level of transparency and accountability in the management of School Operational Assistance funds in remote schools in the Bermani Ilir and Muara Kemumu Districts, Kepahiang Regency. Using a qualitative approach and a case study method, this research collected data through in-depth interviews, observations, and document studies. The research findings indicate that the transparency of BOS fund management in these two districts is still low, as evidenced by the limited public access to financial reports and the low participation of school committees. On the other hand, the accountability of school managers is quite good, but they face constraints in timely reporting and limited human resources. Furthermore, constraints in the use of technology also hinder the effectiveness of financial reporting. To improve transparency and accountability, this study recommends increasing training for school managers and implementing information technology. The results of this study can serve as a basis for developing better BOS fund management policies in remote areas.